2015
DOI: 10.5539/gjhs.v8n5p96
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Marital Satisfaction in Infertile Couple: A Comprehensive Literature Review

Abstract: Background:Many factors impact on marital satisfaction. Related factors include demographic factors, assisted reproductive techniques, psychological health, quality of life, psychological, socioeconomic and family support, and sexual function.Methods:This study is a literature review of research studies conducted on factors associated with marital satisfaction in infertile couples. The current literature review search was undertaken using multiple databases selected from articles pertinent to the study. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
1
32
0
6
Order By: Relevance
“…Average marriage duration is 4,72 (SD= 3,81) (1-21) years and more than half of the participants (%73,8) are married for 1 to 5 years. The average marriage age of men within the scope of the study is 25,73 (SD= 3,81) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) whereas it is 23,21 (SD= 4,89) (16-33) on average for women. Average monthly income of the couples participated is 1478,12 (approximately 500 $) (SD= 810,19) (300-4000) TL; and 67.4% of the couples think the income they earn affords their expenses whereas 32.6% of them do not consider that the income is sufficient for the expenses.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Average marriage duration is 4,72 (SD= 3,81) (1-21) years and more than half of the participants (%73,8) are married for 1 to 5 years. The average marriage age of men within the scope of the study is 25,73 (SD= 3,81) (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) whereas it is 23,21 (SD= 4,89) (16-33) on average for women. Average monthly income of the couples participated is 1478,12 (approximately 500 $) (SD= 810,19) (300-4000) TL; and 67.4% of the couples think the income they earn affords their expenses whereas 32.6% of them do not consider that the income is sufficient for the expenses.…”
Section: Resultsmentioning
confidence: 94%
“…However, in some studies the dissatisfaction was attributed to men. It was stated that if the infertility factor is man, emotional responses get more negative since the infertile men suffer from more stress in their marital relationship 33,35 . While no difference between the sexes was found in the study by Tüzer et.al., in this study the marital satisfaction of men has been found to be significantly lower in comparison to women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Samadaee‐Gelehkolaee et al. () indicated that men's role in infertility has a more negative impact on the couple's satisfaction than women's because men have less tendency to express their problems, which leads them to lower tolerance of the psychological burden. Moreover, these authors also noted a greater tendency in men to consider infertility almost the same as a reduction of their masculinity, which can lead to fear of stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Some couples consider having children early in their marriage a threat to the chance of being alone with their spouse and enjoying their freedom, pursuing fun activities, traveling and spending time together, and thus delay their childbearing decision-making. Moreover, the uncertainty about fully knowing one's spouse (especially in the case of traditional marriages) and feelings of doubt about the stability of the marital relationship caused by disputes and consuming discussions over the course of getting to know one another lead to childbearing hesitations (Kariman et al, 2014b;Kariman et al, 2014a;Testa et al, 2012;Kariman et al, 2015;Klobas, 2011;Rijken, 2009;Samadaee-Gelehkolaee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%